PERFORMANCE IMPROVEMENT MODEL: COMMITMENT DEVELOPMENT BASED ON EMPOWERING AND ORGANIZATIONAL LEARNING - Suhermin Suhermin; Gogi Kurniawan; Abdul Talib Bon; Riza Bahtiar Sulistyan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2023)
Regulatory changes during the pandemic, following high industrial growth in the goods and services sector, have encouraged companies to increase their competitiveness. Then achieving performance becomes a top priority, and the company also requires a strong commitment from its employees. Efforts that are considered relevant are employee empowerment and environmental conditioning of the company as a learning organization. This study aims to analyze the effect of employee empowerment and learning organizations on increasing organizational commitment and performance. The sample used was 158 employees of PT. ACS, as the product and service company in the food and beverage sector. Data collection instruments used a Likert scale and were analyzed using a structural equation model (SEM). The results of the study show that employee empowerment and learning play an important role in increasing organizational commitment and performance. The existence of high commitment will also lead to high employee performance. An important implication of this research is that good empowerment and learning will increase organizational commitment, and a good impact on the organization, namely employee performance will also increase.